Competitive Equilibrium with Type Convergence in an Asymmetrically Informed Market - Thakor, Anjan V. (Review of Financial Studies, 1989)
This article studies an asymmetric information game with "type convergence, " in which, under some realizations of a common uncertainity, inducing informed agents to reveal their types through self-selection by contract choice is either costly or impossible. Under other realizations, self-selection permits costless distinctions between informed agents. I obtain sufficient conditions under which contracting with options prior to the realization of the common uncertainity leads to the existence of a perfectly separating, costless Nash equilibrium. Applications to variable rate loan commitments and life insurance contracting are discussed. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.